Identifying the informal - Nielsen, Ola (2008)
The world is getting closer, we are experiencing a time where we, if we want, can acquire information about everything. But regardless of this flow of information there are still blank spots on the map. But these spots are no longer made up of vast plains or dense tropical forests. The new unknown is situated in the outskirts of our cities, here in what we refer to as the slums the life for millions is going on without any available information. At the same time this lack of information, lack of planning is what makes the slums the informal city. In the informal city life goes on outside the formal systems, for some the slum is a place to sleep when not going to a formal work, for others the entire life is lived in the slum. To investigate a slum are and trying to understand its conditions from a landscape perspective can help us understand and in the long run improve the life in the slums. To go beyond the clearly visible structures and look at how the slum is functioning can be a way to investigate the informal city.